EFFECT OF NATUROPATHY AND PREKSHA MEDITATION ON RHEUMATOID ARTHRITIS PATIENTS - Uttam Nikita, Pradyumna Singh Shekhawat (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2016)
Aim- Present study was aimed to find out the effect of yoga (Yogic kriya of whole body) Preksha Meditation and naturopathy in improvement of joint movement and disability by measuring Range of Motion (ROM), Health Assessment Questionnaire (HAQ) and Rheumatoid Factor (RF) in patients with Rheumatoid Arthritis. The goal of treatment was regression of symptom like Joint pain, swelling, muscle weakness.